Evaluation of assessment method for the trait Spirit in breeding field tests for Icelandic horses - Sigurðardóttir, Heiðrún (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2016)
The temperament trait Spirit is included in the official breeding goal for Icelandic horses. Spirit is subjectively assessed at breeding field tests, and is included in the genetic evaluation for Icelandic horses. The assessment method for spirit has been discussed within the Icelandic horse society for several years where some consider it to favour nervous and tense horses instead of cooperative and stable horses. In 2014, the Horse Breeders Association in Iceland initiated a project for a trial period with additional assessments pertaining to temperamental suppleness by breeding judges at breeding field tests, as means to improve the assessment of spirit. The aim of this thesis was to evaluate the current assessment method for spirit. Genetic parameters were estimated for all temperament traits assessed at breeding field tests as well as general temperament traits assessed at home by owners. The consistency between assessments made by breeding judges and riders at breeding field tests was investigated, as well as the consistency between assessments made by owners at home and assessments made by breeding judges at breeding field tests. The frequency of culling due to temperament faults was also investigated by gathering information from owners of culled horses. The estimated heritabilities of the temperament traits assessed at breeding field tests ranged from 0.00 to 0.76, and differed depending on whether riders or judges assessed the trait. It seemed that the riders were better suited to assess some traits. It was concluded that the new suppleness traits assessed at breeding field tests provide additional information supporting the assessment of spirit but trait definitions need to be improved. Estimated heritabilities for general temperament traits ranged from 0.00 to 0.56. The highest heritability was estimated for training level which describes the genetic potential of the horse to respond to training. Genetic correlations between the general temperament traits and spirit were estimated on a wide range (0.01-0.97) where some traits pertaining to general nerve strength and training response were negatively correlated to spirit. It was concluded that the score for spirit describes only part of the general temperament of the horse. Nevertheless the majority of horse owners in this study were satisfied with the assessment method for spirit. Approximately one third of culled horses were culled at least partly due to temperament faults whereof the majority were young horses that were withdrawn from further training. These results may indicate a strong preselection based on temperament during the process of breaking in young horses.